3D Printing: Controlling Material Reactivity Using Architecture (Adv. Mater. 10/2016). Issue 10 (March 2016) - Sullivan, Kyle T.; Zhu, Cheng; Duoss, Eric B.; Gash, Alexander E.; Kolesky, David B.; Kuntz, Joshua D.; Lewis, Jennifer A.; Spadaccini, Christopher M.
Abstract : Additive manufacturing, or 3D printing, has demonstrated great promise as a means for tailoring material behavior. To date, most studies have focused on improving the mechanical properties, and testing is often performed quasi‐statically. On page 1934, K. T. Sullivan and co‐workers demonstrate that 3D printing can be used to tailor the dynamic behavior of materials, so long as the feature sizes are made commensurate with the length scale of the governing phenomena.